Expanding the Role of Thyroid-Stimulating Hormone in Skeletal Physiology - Baliram, Ramkumarie; Latif, Rauf; Zaidi, Mone; Davies, Terry F. (Frontiers in Endocrinology, 2017)
The dogma that thyroid stimulating hormone (TSH) solely regulates the production of thyroid hormone from the thyroid gland has hampered research on its wider physiological roles. The action of pituitary TSH on the skeleton has now been well described; in particular its action on osteoblasts and osteoclasts. It has also been recently discovered that the bone marrow microenvironment acts as an endocrine circuit with bone marrow resident macrophages capable of producing a novel TSH-β subunit variant (TSH-βv) which may modulate skeletal physiology. Interestingly, the production of this TSH-βv is positively regulated by T3 accentuating such modulation in the presence of thyroid overactivity. Furthermore, a number of small molecule ligands acting as TSH agonists which allosterically modulate the TSH receptor have been identified and which may have similar modulatory influences on bone cells suggesting therapeutic potential. This review summarizes our current understanding of the role of TSH, TSH-β, TSH-βv and small molecule agonists in bone physiology.